Aktivitas Ekspor dan Inefisiensi Teknis Industri Andalan Ekspor Indonesia - Rustiawati, Rika BettyNurindah; Lubis, Andi Fahmi (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
This study examines the effect of export activity on the technical inefficiency by using firm level panel data taken from Annual Survey of Manufacturing conducted by BPS for the period 2010 to 2014 and focus on Indonesia’s mainstay export industry which classified into low technology and high technology sector. A stochastic frontier model with one stage approach is applied to the translog production function to estimate firm level technical efficiency. The findings support the theoretical implications of the positive impact of export activities on firm’s efficiency and low technology sectors have higher efficiency rate than high technology sectors.